Media Usage Motivations and Netflix Video Viewer Satisfaction in East Java - Abadi, Totok Wahyu; Refisca, Syania Fidya; Febriana, Poppy; Sobirov, Bobur (Universitas Negeri Surabaya, 2025)
Netflix is a subscription-based video streaming platform that offers a selection of films and documentaries each month. During the COVID-19 pandemic, streaming services experienced significant growth. This study examines the influence of Netflix media usage motivation on viewer satisfaction in East Java. It applies Guo and Chan-Olmsted’s Video Streaming Platform Representation Theory, McQuail’s Media Usage Motivation Theory, Blumer and Katz’s Uses and Gratification Theory, McMillan’s Interactivity Perception Theory, and Satisfaction Theory. Using a quantitative explanatory method, data were collected through an online questionnaire from 190 respondents and analysed using SPSS 26 and AMOS 22 with Structural Equation Modelling (SEM). The results indicate that Video Streaming Platform Representation, Media Usage Motivation, and Perception of Interactivity significantly influence viewer satisfaction, both simultaneously and partially. Media usage motivation—covering information seeking, personal identity, social integration, and entertainment—shows the most substantial effect. Viewers are satisfied because Netflix provides engaging information about new films and opportunities for interaction among users. The novelty of this study lies in distinguishing new media like Netflix from mainstream media, emphasising how streaming platforms enable users to access entertainment and exchange film- related information within online communities.